Nickel Oxide Electrode Interlayer in CH3NH3PbI3 Perovskite/PCBM Planar‐Heterojunction Hybrid Solar Cells. (31st March 2014) - Jeng, Jun‐Yuan; Chen, Kuo‐Cheng; Chiang, Tsung‐Yu; Lin, Pei‐Ying; Tsai, Tzung‐Da; Chang, Yun‐Chorng; Guo, Tzung‐Fang; Chen, Peter; Wen, Ten‐Chin; Hsu, Yao‐Jane
<x xml:space="preserve">Abstract</x> This study successfully demonstrates the application of inorganic p‐type nickel oxide (NiOx) as electrode interlayer for the fabrication of NiOx/CH3NH3PbI3 perovskite/PCBM PHJ hybrid solar cells with a respectable solar‐to‐electrical PCE of 7.8%. The better energy level alignment and improved wetting of the NiOx electrode interlayer significantly enhance the overall photovoltaic performance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>